A decomposition analysis of wage inequality in the Philippines - Chow, Neriza C. (Animo Repository, 2019)
The data suggests that, in the Philippines, the wage gap between the 90th (highincome earners) and 50th percentile (middle-income) wage groups has been declining. As such, we aim to study this upper-tail wage inequality further by decomposing wage data using the October rounds of the Philippine Labor Force Survey (LFS) from 2007 to 2017 and by looking at trends in wages and employing two mutually exclusive methods. For the trend in relative wage changes, we observe that between the 90th and 50th percentiles of the wage distribution, the wage gap increased from 2007 to 2012 and decreased from 2012 to 2017. For the daily log wages for 2007 and 2017, we find that female workers belonging to the upper half of the wage distribution earn higher than males. In performing a simple regression, we find that 90-50 wage gap among each sub-group of gender, location and educational attainment is decreasing from 2011 to 2017. Furthermore, the 90-50 wage gap among nonNCR workers is greater than the 90-50 wage gap among NCR workers. A similar result is found between the wage gap among males and females, with a higher disparity for the former. For the standard variance decomposition method, the results show that overall variability in female wages explained by age, education and region is 48 to 55%. However, the overall and upper half variability in wages of males, NCR workers, non-NCR workers, high school graduates and college graduates are better explained by other factors (“within” variables) such as work experience or the worker’s type of job.